2022
DOI: 10.1177/14773708221081017
|View full text |Cite
|
Sign up to set email alerts
|

Culture and corruption: An experimental comparison of cultural patterns on the corruption propensity in Poland and Russia

Abstract: The development of effective anti-corruption measures relies on a sound understanding of underlying country-specific cultural patterns of corruption. However, finding these patterns faces the problem of ecological fallacies when tracing back the results of comparative macro-studies to the national level or of using ex-post explanations for cultural variances in experimental research designs. Thus, we ask how cultural patterns can explain country differences in the propensity to act corrupt without neglecting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 99 publications
0
3
0
Order By: Relevance
“…Popular indices, such as Transparency International's Corruption Perceptions Index (CPI), have been criticized for being business-centric and culture-blind by their survey design. 64 The uniformity of the indices makes it an unreliable tool for capturing cultural variance and complexities. 65 As Bamidele 66 argues, certain types of corruption, such as favoritism or string-pulling, can only be meaningfully examined in specific sociocultural contexts.…”
Section: A Cultur Al and Cross -Cultur Al Re Vie W Of Corrup Tionmentioning
confidence: 99%
See 1 more Smart Citation
“…Popular indices, such as Transparency International's Corruption Perceptions Index (CPI), have been criticized for being business-centric and culture-blind by their survey design. 64 The uniformity of the indices makes it an unreliable tool for capturing cultural variance and complexities. 65 As Bamidele 66 argues, certain types of corruption, such as favoritism or string-pulling, can only be meaningfully examined in specific sociocultural contexts.…”
Section: A Cultur Al and Cross -Cultur Al Re Vie W Of Corrup Tionmentioning
confidence: 99%
“…However, a key limitation of these studies concerns the use of a simple high‐low measurement of the level of corruption across countries. Popular indices, such as Transparency International's Corruption Perceptions Index (CPI), have been criticized for being business‐centric and culture‐blind by their survey design 64 . The uniformity of the indices makes it an unreliable tool for capturing cultural variance and complexities 65 .…”
Section: A Cultural and Cross‐cultural Review Of Corruptionmentioning
confidence: 99%
“…The study also found that trust in others is negatively correlated with corrupt behavior, and that trust levels are higher in Poland than in Russia. The authors conclude that cultural factors should be taken into consideration when designing anti-corruption policies and programs [25].…”
Section: Culture and Corruptionmentioning
confidence: 99%
“…The fundamental premise is that individuals choose their actions in consideration of the likely choices of others, and this means that their concrete social relations are critical to their actions. If the tone set by top management upholds ethics and integrity, employees will be more inclined to follow those same ethical values (Kassem, 2022;Fürstenberg et al, 2022). We expect, when employees perceive that the organisation is invested in maintaining a relationship with them as a result of its ethical culture and transparent communication, they may feel a desire to comply with internal controls (Thelen and Formanchuk, 2022;Martínez et al, 2021).…”
Section: Dynamics and Control Of Occupational Fraudmentioning
confidence: 99%